Pengaruh Suasana Toko Terhadap Minat Beli Konsumen Pada UD. Sinar Anugerah Pratama Manado - Jeremia Alfredo Paila; John A. F. Kalangi; Joula J. Rogahang (JURNAL ADMINISTRASI BISNIS, 2018)
Store atmosphere is a physical characteristic that is very important for every business and can affect the feelings or moods of consumers who visit the store, thereby affecting the interest to buy. Buying interest is a desire to buy a product or service to be purchased. In every business activity, basically aims to gain maximum profit in order to maintain the exsitence of the company amid the competition. The goal to be achieved in this research is to know the magnitude of the influence of store atmosphere on consumer buying interest in UD. Sinar Anugerah Pratama Manado. The research is a kind of quantitative research. Independen variable (x) is the store atmosphere and the dependent variable (y) buying interest. The population of this research is all visitor in UD. Sinar Anugerah Pratama Manado. Assuming the population in this study is not limited. Sampling in this study using purposive sampling method, data collection techniques used in this study is a questionnaire. Samples drawn from a population of 50 respondents consisting of 72% female and 28% male. Hypothesis testing in this study using parametric statistics in the form of t-test to see how the influence of each independent variable individually to the dependent variable. And the f-test to see how the influence of all independent variables together on the dependent variable. The value of f-arithmetic of 8.519 with the significance p-value = 0.005 < 0.05 indicates that there is a simultaneous significant influence of the store's atmosphere on buying interest. The value of t-arithmetic of 2.919 with significance p-value = 0.005 < 0.05 indicates that there is a partial significant influence of the independent variable to the dependent variable. This means that there is a strong relationship that gives effect to buy interest to consumers. From the results of hypothesis testing above shows there is significant influence of store atmosphere to consumer buying interest in UD. Sinar Anugerah Pratama Manado. Keywords: Store atmosphere, buying interest.